Organizational Commitment - Gupta, B. L. (Journal of Engineering Education Transformations, 1999)
The paper describes the importance of organizational commitment. The characteristics of organizational commitment and its output are mentioned. Reasons for poor organizational commitment are identified on the basis of experiences and discussion with various managers working in the field. Various broad based strategies are described out of which a strategy mix can be selected for enhancing organizational commitment in specific situation.